(untitled) (Journal of Kidney Cancer, 2021)
The aim of the present study was to investigate the rs1800468 (G-800A), rs1800469 (C-509T), rs1800470 (C29T), and rs1800471 (G74C) TGFB1 genetic polymorphisms and their haplotype structures in patients with Wilms Tumor (WT) and neoplasia-free controls. The genomic DNA was extracted from 35 WT patients and 160 neoplasia-free children, and the TGFB1 polymorphisms were genotyped by polymerase chain reaction, followed by restriction fragment length polymorphism. The haplotype structures were inferred, and permutation and logistic regression tests were performed to check for differences in haplotype distribution between the control and WT individuals. Positive associations were found in the recessive model for rs1800469 T allele (OR: 8.417; 95% CI: 3.177 to 22.297; P < 0.001) and for the rs1800470 C allele (OR: 3.000; 95% CI: 1.296 to 6.944; P = 0.01). Haplotype analysis revealed a significant negative association between GCTG and WT (OR: 0.236, 95% CI: 0.105 to 0.534; P = 0.0002); by contrast, the GTTG haplotype was associated with increased risk for WT (OR: 12.0; 95% CI: 4.202 to 34.270; P < 0.001). Furthermore, rs1800469 was negatively correlated with tumor size and a trend toward a positive correlation for capsular invasion was observed in the dominant model (Tau-b: −0.43, P = 0.02 and tau-b: 0.5, P = 0.06, respectively). This is the first study with rs1800468, rs1800469, rs1800470, and rs1800471 TGFB1 polymorphisms in WT, and our results suggest that the TGFB1 promoter and signal peptide region polymorphisms may be associated with WT susceptibility and clinical presentation.